Weaving new social stories in Itaipu: Proposal for a citizen museum documentation (Cadernos de Sociomuseologia, 2022)
The research is dedicated to examining the documentation produced in museums, ap- plying the concepts of power, knowledge and discourse present in the intellectual trajectory of the French philosopher Michel Foucault. Aiming to understand the discursive practices of the field, it analyzes the subjects and the creation of documentary procedures in collections and museums, at certain historical moments, in addition to the reference documents produced by the international organizations for the protection of the world and heritage. In a special way, it maps and explores the entire production of the scientific journal Cadernos de Sociomuseologia searching for theoretical and practical discussions about documentation. Taking as a case study the Itaipu Archaeological Museum, proposes, tests and evaluates a documentation model for museums committed to the theoretical and practical principles of Social Museology. The pro- posed model should be able to enhance the knowledge and individual and collective memories related to the territory in which the museum institution is inserted. In addition, it should provide for the development of information retrieval instruments, quantitative and qualitative indicators for the evaluation or construction of the Collections Development Policy, Documentation Pol- icy and for the Museological Plan.Key words: museum documentation; participatory inventory; Itaipu Archeology Museum; Social Museology; Sociomuseology